Enhancing oxygen savings and carbon dioxide purity in biomass oxy-circulating fluidized bed combustion with an oxygen carrier. (15th February 2023) - Ju Kim, Seong; Hong Moon, Ji; Jo, Sung-Ho; Jin Park, Sung; Young Kim, Jae; Uk Beak, Geon; Hee Yoon, Sang; Ryu, Ho-Jung; Won Ra, Ho; Jun Yoon, Sang; Yoon, Sung-Min; Goo Lee, Jae; et al.
Graphical abstract: Highlights: Oxygen carrier is applied to supply some O2 in a biomass OCA-Oxy-CFBC. CO emissions decrease to 59% when silica sand is replaced with iron ore. Adding an oxygen carrier achieved an O2 saving of 4.86% CO2 purity increased to 97.4% without reduction of combustion efficiency. Abstract: A pure oxygen (O2 ) supply for oxy-fuel combustion causes excessive power consumption and decreased net plant efficiency. The oxygen carrier-aided oxy-circulating fluidized-bed combustion (OCA-Oxy-CFBC) process can facilitate reduction in the O2 supply requirement. Moreover, the use of an oxygen carrier, instead of silica sand, as bed materials may improve oxygen transport in the combustor, leading to a reduction in the pure O2 supply required. This study aimed to investigate the effect of oxygen carrier addition on Oxy-CFBC characteristics, including temperature, pressure, solid suspension density, pollutant emissions, combustion efficiency, and O2 reduction for stable operation. As an oxygen carrier, iron ore was introduced into the downcomer pipeline using a dedicated hopper during the biomass Oxy-CFBC process under low excess O2 conditions. Although the O2 concentration in the flue gas decreased by 1.7 vol%, the CO emissions decreased from 6.8 mg/MJ to 2.8 mg/MJ when the silica sand was replaced with 33 wt% iron ore. Furthermore, the CO2 purity in the flue gas improved from 94.3 vol% to 95.7–97.4 vol% under a lower equivalence ratio (1.01–1.07) during stable OCA-Oxy-CFBC operation. Consequently, oxygen can be transported and supplied by adding an oxygen carrier during the biomass Oxy-CFBC operation, indicating O2 savings of 4.86 % for the total amount of O2 required.